Parental strategies that support adults with intellectual disabilities to explore decision preferences, constraints and consequences. Issue 2 (3rd April 2022) - Bigby, Christine; Douglas, Jacinta; Smith, Elizabeth; Carney, Terry; Then, Shih-Ning; Wiesel, Ilan
ABSTRACT: Background: Supporting participation in decision making is complex, dynamic and multifactorial. The aim of this study was to understand more about the difficulties parents of adults with intellectual disabilities experienced in providing decision support and their strategies for resolving them. Method: Participants were 23 parents who regularly provided decision support for their adult with intellectual disabilities. Most of the adults (19) lived at home. Parents participated in semi-structured interviews at least three times during the study. We applied a social-constructionist theoretical perspective and a template approach for analysis. Results: Findings fell into three core categories, making the right decision, factors that made decision support difficult, and strategies to manage uncertainty, which included controlling, influencing, expanding the adult's horizons and enabling risk. Conclusions: The knowledge gained will help in building the capacity of parents to provide decision support that better understands and respects the will and preferences of the person they support.